A Handbook for Data Analysis in the Behavioral Sciences / Methodological Issues - Keren Gideon; Lewis Charles (Lawrence Erlbaum Associates, Publishers, 1993)
Preface, Models and Measurement, Mathematical Models in Psychology, What Is and Isn't Measurement, Multidimensional Scaling, Methological Issues, Rational Appraisal of Psychology Research and the Good-Enough Principle, Between or Within-Subjects Design: A Methodological Dillema, Intuitive Statistics, Belief in the Law of Small Numbers, The Perception of Randomness, On Generating Random Sequences, Hypothesis Testing and Power and Effect Size, How Significant is ''Significance'', Effect Size, The Relative Power of Parametric and Nonparametric Statistical Methods, Cumulating Evidence, Author and Subject Index.